Strategi Perpustakaan dalam Menerapkan Kesehatan dan Keselamatan Kerja di Perpustakaan UIN Ar-Raniry pada masa Adaptasi New Normal - Safri, T Mulkan; Subhan, Adi; Syukrinur, Syukrinur (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2023)
The health and safety of librarians is an obstacle in realizing excellent service performance in libraries, especially during the adaptation period of new habits. This is the basis for this writing. This study aims to determine the strategies and constraints of the UPT Library of Ar-Raniry Banda Aceh in implementing the occupational health and safety of librarians during the adaptation period of new habits. This study uses qualitative research methods, namely data collection is done by interview, observation and documentation. The subjects of this study were the head of the library and the librarian of the UPT Library of UIN Ar-Raniry. The results showed that the policy of the UPT Library of UIN Ar-Raniy was good, but the standards and provision of infrastructure that supported the health and safety of librarians during the adaptation period to new habits were still not optimal. Thus, the UPT Library of UIN Ar-Raniry needs to review and improve the provision of occupational health and safety facilities for librarians.